Hydrological Effects on Rock Mass Quality and Rippability of Heterogeneous Karstic Limestone - Andy Erwin Wijaya; Partama Misdiyanta; Rizqi Prastowo; Yoshitaka Mitsui; Keodouangdy Yongthong; Berwyn Dzaky Radhitya (International Journal of Hydrological and Environmental for Sustainability, 2026)
The proposed study area is located approximately 1.9 km southwest of the main cement plant in Tuban, Indonesia. This research aims to evaluate the rippability characteristics of the limestone formation underlying the planned development site. The assessment is based on data obtained from a geotechnical borehole investigation (CR-1), integrated with previous subsurface exploration results. The site is designated for shallow foundation systems designed to withstand bearing pressures ranging from 300 to 800 kPa. Subsurface conditions are characterized by karstic limestone with complex hydrogeological features. The limestone exhibits high sensitivity to water infiltration, dissolution processes, and mechanical property degradation under saturated conditions. Significant spatial variability in rock mass quality and strength is observed over relatively short vertical and horizontal distances. The uppermost layer comprises residual lateritic (red) soil derived from in-situ weathering of the underlying limestone. The presence of limestone gravels and boulders within the residual soil indicates a transitional interface between the overburden and the more competent limestone strata. The limestone formation consists of heterogeneous materials, including highly porous honeycomb-textured rock and relatively intact, sound limestone, distributed irregularly across the site. This heterogeneity results in considerable variability in mechanical strength and excavation response. The findings provide essential insights into the rippability behavior of the limestone and its implications for foundation design and construction planning in karst environments.